Economic Recovery: The Role of Business Digitization in Minimizing Unemployment During the Covid-19 Pandemic - Muhammad Ihsaan Rizqulloh (CV. Literasi Indonesia, 2021)
Business digitization is the change of communication, interaction, and business functions to digital. In business applications, digitization changes the business processes, functions, and business models applied to digital technology. One of the most successful ways to deal with the digital revolution is business digitization in the 5.0 society era. The concept of society 5.0 is related to the National Economic Recovery, which aims to build a human-centered society where economic development and problem-solving can be achieved. The role of business digitization during the Covid-19 pandemic is very influential on the Indonesian economy, especially for government programs that have used digital systems and supported Small and Medium Enterprises (MSMEs). This study uses a qualitative descriptive approach, using secondary data obtained from the Central Statistics Agency, journals, books, and other sources relevant to the research. Based on the research results, there is a very significant change in business digitization in the era of society 5.0, where digital business is more promising than conventional concepts.